Toothbrushing And Dietary Behavior of Children Aged 3–6 Years with Early Childhood Caries in Impoverished Community of Semampir District, Surabaya - Ardianti Maartrina Dewi; Satiti Kuntari; Tania Saskianti; Berliana Ayu Prawesti Permatasari; Adinda Putri (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: This research aimed to observe tooth brushing and dietary behavior of children aged 3–6years with early childhood caries (ECC) in impoverished communities, Semampir District, Surabaya City.Materials and Methods: This was descriptive observational with cross-sectional design study in 50 samplesof mother whom their children diagnosed with ECC. Research instrument using questionnaires based oncaries risk assessment (CRA) which modified. Results: Most samples showed good tooth brushing behavior,which includes brushing frequency and duration, routines using toothpaste, had tooth brushing initiative andindependently brushing teeth. The majority of samples had poor dietary behavior which includes snackinghabit frequency, time management, fruit and milk consumption. Conclusion: Most children aged 3–6 yearsin impoverished communities, Semampir District of Surabaya already had good brushing teeth behavior, butthey had poor diet which explain high prevalence of caries.